Effect of eco-friendly management of golf clubs on golfers’ behavioral intention to return: green image, perceived quality as mediator and green marketing as moderator - Jeong, Kwon-Hyuk; Song, Jeongmyeong (Frontiers in Psychology, 2025)
IntroductionAmid growing concerns about environmental sustainability, the sports and leisure industry has seen increased interest in green management practices. However, few empirical studies have explored how such practices influence consumer behavior in golf clubs. This study addresses that gap by examining how eco-friendly management affects golfers’ behavioral intention to revisit. Specifically, the study investigates the mediating roles of green image and perceived quality, and the moderating effect of green marketing in this relationship.MethodsTo empirically test the proposed model, data were gathered from 252 South Korean golfers using structured field surveys. The questionnaire measured five constructs: eco-friendly management, green image, perceived service quality, green marketing exposure, and behavioral intention. Analytical methods included frequency analysis, confirmatory factor analysis (CFA) to test construct validity, reliability testing (Cronbach’s α), descriptive statistics, and Pearson’s correlation. To test mediation and moderation effects, regression-based analyses were conducted using Hayes’ (2013) PROCESS macro.ResultsThe statistical findings revealed three key insights. First, green image fully mediated the effect of eco-friendly management on behavioral intention, implying that consumers’ perception of the club’s environmental responsibility significantly influences their revisit decisions. Second, perceived quality also acted as a full mediator, indicating that environmental initiatives enhance service evaluations, thereby affecting loyalty behavior. Third, green marketing moderated the relationship between eco-friendly management and green image, suggesting that when marketing efforts are more active and visible, the positive impact on green image is amplified.DiscussionThis research offers valuable contributions to the literature on environmental psychology and sustainable service management. It uncovers the psychological mechanisms—specifically green image and perceived quality—through which eco-friendly practices influence consumer behavior. Moreover, it highlights the role of green marketing in shaping environmental perceptions. For golf clubs aiming to enhance customer retention, this study suggests that sustainability initiatives must be effectively communicated and designed to improve both image and service quality. The results underscore the strategic importance of aligning operational greening with targeted environmental messaging.